2008
DOI: 10.1002/jmv.21340
|View full text |Cite
|
Sign up to set email alerts
|

Increased frequency of CD56Bright NK‐cells, CD3CD16+CD56 NK‐cells and activated CD4+T‐cells or B‐cells in parallel with CD4+CDC25High T‐cells control potentially viremia in blood donors with HCV

Abstract: A detailed phenotypic analysis of major and minor circulating lymphocyte subsets is described in potential blood donors with markers of hepatitis C virus (HCV), including non-viremic and viremic groups. Although there were no changes in the hematological profile of either group, increased the levels of pre-NK cells (CD3 CD25High T-cells were significantly elevated in both the viremic and nonviremic groups, it was particularly evident in the viremic low viral load subgroup. A parallel increase in CD4 þ CD25 Hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
18
0

Year Published

2009
2009
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 53 publications
3
18
0
Order By: Relevance
“…The current study found a reduced frequency of NK cells in post-hepatitis cirrhosis which is in agreement with previous research indicating an inadequacy of innate host response and inefficient initiation of adaptive immune response [9, 10]. We also showed that no difference was found between the nonviremic and viremic groups, which is inconsistent with the results of Zarife et al [7]. Different methodologies, including the CD45 labeling, smaller sample sizes, and differences in severity of disease, might explain why some of the findings in these studies differed from ours.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…The current study found a reduced frequency of NK cells in post-hepatitis cirrhosis which is in agreement with previous research indicating an inadequacy of innate host response and inefficient initiation of adaptive immune response [9, 10]. We also showed that no difference was found between the nonviremic and viremic groups, which is inconsistent with the results of Zarife et al [7]. Different methodologies, including the CD45 labeling, smaller sample sizes, and differences in severity of disease, might explain why some of the findings in these studies differed from ours.…”
Section: Discussionsupporting
confidence: 78%
“…Following incubation, erythrocytes were lysed using 1 ml FACS lysing solution (eBioscience Inc., USA). The cells were washed twice with 2 ml PBS buffer [7]. …”
Section: Methodsmentioning
confidence: 99%
“…Significant alterations in NK subsets in patients with chronic HCV infection compared with individuals who resolved the infection and healthy controls have been described (Golden-Mason et al, 2006). Phenotypic analysis of NK cells in HCV non-viremic and viremic groups suggests that elevated levels of CD56 Bright NK cells, together with pre-NK cells and activated CD4 + T-cells in combination with CD4 + CD25 High T-cells, is associated with viremia control (Zarife et al, 2009). …”
Section: Discussionmentioning
confidence: 99%
“…90%) of NK cells are CD56 dim , whereas approximately 10% of NK cells are CD56 bright [1]. NK cells lacking CD56 expression are rare in healthy donors, were originally described in HIV-infected individuals [21,22] and have more recently been found at elevated levels in other chronic infectious diseases, such as hepatitis C [23,24] and Chagas disease [25]. However, in these settings, NK cells lacking CD56 expression are functionally defective as they display decreased levels of activating receptors and fail to kill target cells.…”
Section: Discussionmentioning
confidence: 99%